Sex-Selective Abortions, Fertility, and Birth Spacing - Portner, Claus C. (World Bank Group, Washington, DC, 2015)
Previous research on sex-selective abortions has ignored the interactions between fertility, birth spacing, and sex selection, despite both fertility and birth spacing being important considerations for parents when deciding on the use of sex selection. This paper presents a novel approach that jointly estimates the determinants of sex-selective abortions, fertility, and birth spacing, using data on Hindu women from India's National Family and Health Surveys. Women with eight or more years of education in urban and rural areas are the main users of sex-selective abortions and they also have the lowest fertility. Predicted lifetime fertility for these women declined 11 percent between the 1985-1994 and 1995-2006 periods, which correspond to the periods of time before and after sex selection became illegal. Fertility is now around replacement level. This decrease in fertility has been accompanied by a 6 percent increase in the predicted number of abortions during the childbearing years between the two periods, and sex selection is increasingly used for earlier parities. Hence, the legal steps taken to combat sex selection have been unable to reverse its use. Women with fewer than eight years of education have substantially higher fertility and do not appear to use sex selection.